Stability of isoniazid injection in i.v. solutions. (15th May 2018) - Lee, Jun H.; Moriyama, Brad; Henning, Stacey A.; Danner, Robert L.; Walsh, Thomas J.; Penzak, Scott R.; Grimes, George J.; Potti, Gopal K.
Abstract : Purpose: Results of an assessment of the chemical stability of isoniazid injection in 0.9% sodium chloride injection and 5% dextrose injection are reported. Methods: Triplicate solutions of isoniazid (0.5 and 6.0 mg/mL) in the 2 diluents were prepared in ethylene and propylene copolymer i.v. containers and stored under light protection at room temperature (20–25 °C) or under refrigeration (2–8 °C). Standard aliquots were removed from each solution at time points up to 72 hours and analyzed via high-performance liquid chromatography (HPLC). Stability was defined as retention of >90% of the initial isoniazid concentration; pH, osmolality, and visual appearance were assessed. Results: Isoniazid 0.5- and 6.0-mg/mL solutions in 0.9% sodium chloride injection were stable for up to 72 hours at room temperature or under refrigeration. HPLC analysis of isoniazid 0.5-mg/mL solutions in 5% dextrose injection revealed a decrease to less than 90% of the initial concentration at 8 hours at room temperature and at 30 hours under refrigeration. Isoniazid 6.0-mg/mL solutions in 5% dextrose injection were stable for 24 hours at room temperature and for 48 hours under refrigeration. The pH, osmolality, and visual appearance of the solutions were not affected. Conclusion: Isoniazid solutions of 0.5 and 6.0 mg/mL in 0.9% sodium chloride injection were stable under light protection for up to 72 hours when stored at room temperature or under refrigeration. Isoniazid injection was less stable in 5% dextrose injection, especially at a concentration of 0.5 mg/mL at room temperature.